The Raduga multipurpose ion/plasma source for surface modification of construction materials; Nuclear Instruments and Methods in Physics Research. Sec. B: PART1; Vol. 59-60 - Ryabchikov A. I. Aleksandr Ilyich; Arsubov N. M.; Vasilyiev N. A.; Dektyarev S. V. (1991, 1991)
In this article a repetitively pulsed vacuum arc ion/plasma source for property modification of near-surface layers in construction materials is described. The Raduga ion source provides both high concentration implantation and optimum two-element implantation. These advantages can be achieved by using not only pure single-element or mixed fluxes, but also pulsed beam sequences with controllable composition and energy of each ion species. Another unique feature of the source is its ability to generate a sequence consisting of ion beam and plasma stream pulses. Switching between ion irradiation and plasma deposition can be done from pulse to pulse, within each pulse, or after accumulation of a required dose. Two-element operating conditions provide the possibility of compensating for sputtering during implantation by neutral atom and plasma deposition. The technological capabilities of the source are: (a) single-element ion implantation; (b) multi-element implantation using compositional cathodes; (c) multi-element implantation with beam composition and ion energy controlled during irradiation and even from pulse to pulse; (d) high-concentration implantation; (e) thin-film deposition; and (f) thin-film deposition under ion irradiation conditions.